2018
DOI: 10.1016/j.bpj.2018.10.029
|View full text |Cite
|
Sign up to set email alerts
|

MutSγ-Induced DNA Conformational Changes Provide Insights into Its Role in Meiotic Recombination

Abstract: In many organisms, MutSg plays a role in meiotic recombination, facilitating crossover formation between homologous chromosomes. Failure to form crossovers leads to improper segregation of chromosomes and aneuploidy, which in humans result in infertility and birth defects. To improve current understanding of MutSg function, this study investigates the binding affinities and structures of MutSg in complex with DNA substrates that model homologous recombination intermediates. For these studies, we overexpressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 80 publications
4
21
0
Order By: Relevance
“…Following strand invasion, early recombination intermediates are thought to be stabilized by the MutSγ DNA clamp complex composed of MutS homolog proteins 4 and 5 (MSH4/MSH5) [ 46 , 47 , 64 ]. This stabilizing event is required both for the completion of homolog synapsis and also the downstream formation of meiotic COs. During this process, RAD51/DMC1 foci are typically replaced by MSH4 foci upon normal synapsis [ 7 , 46 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Following strand invasion, early recombination intermediates are thought to be stabilized by the MutSγ DNA clamp complex composed of MutS homolog proteins 4 and 5 (MSH4/MSH5) [ 46 , 47 , 64 ]. This stabilizing event is required both for the completion of homolog synapsis and also the downstream formation of meiotic COs. During this process, RAD51/DMC1 foci are typically replaced by MSH4 foci upon normal synapsis [ 7 , 46 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…A stable MutSg complex would be advantageous in a diploid background but may promote homeologous recombination in a neoallopolyploid. In S. cerevisiae, MutSg stabilizes single-end invasions as well as Holliday junction recombination intermediates (Lahiri et al, 2018). The ability of MutSg to stabilize early recombination intermediates comprising divergent heteroduplex sequences in wheat may have been negated by deletions in MSH5B and MSH4D.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that the human and yeast MutSγ heterodimer can bind to D loops, HJs, single-stranded overhangs and other DNA substrates (Snowden et al 2004; Lahiri et al 2018). Binding to junctions enhances stability of these structures, while binding to single-stranded DNA promotes displacement of the overhang that could potentially allow for nucleoprotein filament formation involving, for example, RPA (Lahiri et al 2018).…”
Section: Introductionmentioning
confidence: 99%